Cathode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery

JP2025027027AActive Publication Date: 2025-02-26PANASONIC HOLDINGS CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024206066
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2024-11-27
Publication Date
2025-02-26
Estimated Expiration
2040-07-28

Smart Images

  • Figure 2025027027000008
    Figure 2025027027000008
  • Figure 2025027027000001
    Figure 2025027027000001
  • Figure 2025027027000002
    Figure 2025027027000002
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte secondary battery with the ratio of Ni to the total number of moles of metal elements excluding Li is 80 mol% or more capable of suppressing the decrease in battery capacity caused by charging and discharging.SOLUTION: The cathode active material for non-aqueous electrolyte secondary batteries contains Ni with 80 mol% or more of the total number of moles of metal elements excluding Li; and Lithium transition metal composite oxide containing at least Al, which includes a surface modification layer containing at least Sr formed on the surface of the primary particles of the lithium transition metal composite oxide, in which Sr does not form a solid solution in the lithium transition metal composite oxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery. [Background technology]

[0002] In recent years, non-aqueous electrolyte secondary batteries have been widely used as high-output, high-capacity secondary batteries, which include a positive electrode, a negative electrode, and a non-aqueous electrolyte and perform charging and discharging by transferring lithium ions between the positive electrode and the negative electrode. From the viewpoint of reducing the resistance and increasing the capacity of the battery, there is a demand for improving the characteristics of a positive electrode active material contained in the positive electrode of the battery.

[0003] For example, Patent Document 1 discloses a positive electrode active material that is a lithium transition metal composite oxide having a layered structure and containing Mn, Ni, Co, Sr, and Mo, in which the Mo content is 0.1 mol % to 1.5 mol % and the Mo / Sr content ratio is 0.5 to 2.0 in molar ratio, thereby achieving high capacity and improved charge / discharge cycle characteristics. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5245210 Summary of the Invention

[0005] Incidentally, in order to obtain a high discharge capacity in the lithium transition metal composite oxide contained in the positive electrode active material, it is possible to design it so that the Ni content is high. However, when the ratio of Ni to the total number of moles of metal elements other than Li is 80 mol % or more, the layered structure of the lithium transition metal composite oxide becomes unstable, and the battery capacity may decrease with charging and discharging. The technology of Patent Document 1 does not take into consideration the decrease in battery capacity with charging and discharging in a battery with a high Ni content, and there is still room for improvement.

[0006] Therefore, an object of the present disclosure is to provide a positive electrode active material in which the ratio of Ni to the total number of moles of metal elements excluding Li is 80 mol % or more, and which suppresses the decrease in battery capacity due to charging and discharging.

[0007] A positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure comprises a lithium transition metal composite oxide containing at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li, and a surface modification layer containing at least Sr formed on the surface of primary particles of the lithium transition metal composite oxide, wherein Sr is not dissolved in the lithium transition metal composite oxide.

[0008] A nonaqueous electrolyte secondary battery according to one aspect of the present disclosure is characterized by including a positive electrode containing the above-described positive electrode active material, a negative electrode, and a nonaqueous electrolyte.

[0009] According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, it is possible to provide a high-capacity nonaqueous electrolyte secondary battery in which a decrease in battery capacity due to charging and discharging is suppressed. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The layered structure of the lithium transition metal composite oxide includes a transition metal layer such as Ni, a Li layer, and an oxygen layer, and the Li ions present in the Li layer reversibly enter and exit, thereby allowing the charge and discharge reaction of the battery to proceed. Here, in the lithium transition metal composite oxide contained in the positive electrode active material, when the ratio of Ni to the total mole number of metal elements other than Li is 80 mol % or more, many Li ions are extracted from the Li layer during charging of the battery, so that the layered structure may become unstable. On the surface of the lithium transition metal composite oxide whose layered structure has become unstable, an altered layer is formed by reaction with the electrolyte. Since the structural change of the lithium transition metal composite oxide proceeds further from the altered layer, the battery capacity gradually decreases with charging and discharging. However, by containing a predetermined amount of Al and Sr as in the positive electrode active material for non-aqueous electrolyte secondary batteries according to one embodiment of the present disclosure, the reaction with the electrolyte on the surface is suppressed by the synergistic effect of Al and Sr, and further, the structure of the surface is stabilized, so that the decrease in the battery capacity with charging and discharging can be suppressed. Since Al does not change its oxidation number during charging and discharging, it is believed that its inclusion in the transition metal layer stabilizes the structure of the transition metal layer. In addition, Sr is believed to be able to change the surface state of the lithium transition metal composite oxide through electronic interactions.

[0012] An example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail below. A cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be exemplified below, but the electrode body is not limited to the wound type, and may be a laminate type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated one by one with a separator interposed therebetween. In addition, the battery case is not limited to a cylindrical shape, and may be, for example, a square shape, a coin shape, or the like, or may be a battery case made of a laminate sheet including a metal layer and a resin layer.

[0013] Fig. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in Fig. 1, the nonaqueous electrolyte secondary battery 10 includes an electrode assembly 14, a nonaqueous electrolyte (not shown), and a battery case 15 that accommodates the electrode assembly 14 and the nonaqueous electrolyte. The electrode assembly 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. The battery case 15 includes a cylindrical outer can 16 with a bottom, and a sealing body 17 that closes the opening of the outer can 16.

[0014] The electrode body 14 is composed of a long positive electrode 11, a long negative electrode 12, two long separators 13, a positive electrode tab 20 joined to the positive electrode 11, and a negative electrode tab 21 joined to the negative electrode 12. The negative electrode 12 is formed to have a size slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer in the longitudinal direction and width direction (short direction) than the positive electrode 11. The two separators 13 are formed to have a size at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example.

[0015] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18, 19 disposed above and below the electrode body 14. In the example shown in Fig. 1, a positive electrode tab 20 attached to the positive electrode 11 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and a negative electrode tab 21 attached to the negative electrode 12 passes outside the insulating plate 19 and extends toward the bottom side of the outer can 16. The positive electrode tab 20 is connected to the lower surface of a bottom plate 23 of the sealing body 17 by welding or the like, and a cap 27 of the sealing body 17 electrically connected to the bottom plate 23 serves as a positive electrode terminal. The negative electrode tab 21 is connected to the inner bottom surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative electrode terminal.

[0016] The exterior can 16 is, for example, a cylindrical metal container with a bottom. A gasket 28 is provided between the exterior can 16 and the sealing body 17, and the internal space of the battery case 15 is sealed. The exterior can 16 has a grooved portion 22 that supports the sealing body 17 and is formed, for example, by pressing the side portion from the outside. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface.

[0017] The sealing body 17 has a structure in which a bottom plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, and the current path between the lower valve body 24 and the upper valve body 26 is interrupted. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.

[0018] The positive electrode 11, negative electrode 12, separator 13 and nonaqueous electrolyte that constitute the nonaqueous electrolyte secondary battery 10 will be described in detail below, in particular the positive electrode active material contained in the positive electrode active material layer 31 that constitutes the positive electrode 11.

[0019] [Positive electrode] The positive electrode 11 has a positive electrode collector 30 and a positive electrode active material layer 31 formed on both sides of the positive electrode collector 30. For the positive electrode collector 30, a foil of a metal, such as aluminum or an aluminum alloy, that is stable in the potential range of the positive electrode 11, or a film having the metal disposed on the surface layer, can be used. The positive electrode active material layer 31 includes a positive electrode active material, a conductive material, and a binder. The thickness of the positive electrode active material layer 31 is, for example, 10 μm to 150 μm on one side of the positive electrode collector 30. The positive electrode 11 can be produced by applying a positive electrode slurry including a positive electrode active material, a conductive material, a binder, and the like to the surface of the positive electrode collector 30, drying the coating, and then compressing it to form the positive electrode active material layer 31 on both sides of the positive electrode collector 30.

[0020] Examples of the conductive material contained in the positive electrode active material layer 31 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode active material layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with carboxymethylcellulose (CMC) or a salt thereof, polyethylene oxide (PEO), and the like.

[0021] The positive electrode active material includes a lithium transition metal composite oxide and a surface modification layer formed on the surface of a primary particle of the lithium transition metal composite oxide. The lithium transition metal composite oxide contains at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li. By making the ratio of Ni to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide 80 mol % or more, a high-capacity battery can be obtained.

[0022] The lithium transition metal composite oxide has a layered structure. Examples of the layered structure of the lithium transition metal composite oxide include a layered structure belonging to the space group R-3m and a layered structure belonging to the space group C2 / m. Among these, a layered structure belonging to the space group R-3m is preferred in terms of high capacity and stability of the crystal structure.

[0023] The ratio of Ni to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide is preferably 90 mol % or more, which allows a battery with a higher capacity to be obtained.

[0024] Lithium transition metal composite oxides are generally represented by the formula Li a Ni x Al y Co z M w O 2-b(wherein, 0.95 < a < 1.05, 0.8 ≤ x ≤ 0.96, 0 < y ≤ 0.10, 0 ≤ z ≤ 0.15, 0 ≤ w ≤ 0.1, 0 ≤ b < 0.05, x + y + z + w = 1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn). The composite oxide can be represented by the above formula. In addition, the positive electrode active material may contain a lithium transition metal composite oxide other than that represented by the above general formula, or other compounds, as long as the object of the present disclosure is not impaired. The molar fraction of the metal element contained in the entire particles of the lithium transition metal composite oxide is measured by inductively coupled plasma (ICP) emission spectrometry.

[0025] It is preferable that a, which represents the ratio of Li in the lithium transition metal composite oxide, satisfies 0.95 ≤ a < 1.05, and more preferably satisfies 0.97 ≤ a ≤ 1.03. When a is less than 0.95, the battery capacity may decrease as compared with the case where a satisfies the above range. When a is 1.05 or more, more Li compound needs to be added as compared with the case where a satisfies the above range, which may not be economical from the viewpoint of production cost.

[0026] It is preferable that y, which represents the ratio of Al to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, satisfies 0 < y ≤ 0.10, and more preferably satisfies 0.03 ≤ y ≤ 0.07. Since the oxidation number of Al does not change even during charge and discharge, it is considered that the structure of the transition metal layer is stabilized by being contained in the transition metal layer. On the other hand, when y > 0.10, Al impurities are generated and the battery capacity decreases. Al may be uniformly dispersed in the layered structure of the lithium transition metal composite oxide, or may be present in a part of the layered structure.

[0027] Co and M (M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn) are optional components. z and w, which indicate the ratios of Co and M to the total number of moles of metal elements other than Li in the lithium transition metal composite oxide, preferably satisfy 0≦z≦0.15 and 0≦w≦0.1, respectively. Since Co is expensive, it is preferable to suppress the content of Co from the viewpoint of production costs.

[0028] The lithium transition metal composite oxide is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particle is, for example, 0.05 μm to 1 μm. The particle size of the primary particle is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM). The surface modification layer exists on the surface of the primary particle. In other words, the surface modification layer exists on the surface of the secondary particle of the lithium transition metal composite oxide, or on the interface where the primary particles contact each other.

[0029] The lithium transition metal composite oxide is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the lithium transition metal composite oxide can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.

[0030] The lithium transition metal composite oxide has a surface layer present from the surface to the inside, and a main body present inside the surface layer. The thickness of the surface layer is, for example, 1 nm to 5 nm.

[0031] The ratio of Al to the total number of moles of metal elements excluding Li in the surface layer is 1.3 times or more the ratio of Al to the total number of moles of metal elements excluding Li in the main body. This makes the structure of the surface layer more stable than that of the main body, and the decrease in battery capacity due to charging and discharging can be suppressed by a synergistic effect with the surface modification layer described later. The ratio of Al to the total number of moles of metal elements excluding Li in the surface layer can be, for example, 4 times or less the ratio of Al to the total number of moles of metal elements excluding Li in the main body.

[0032] The surface modification layer contains at least Sr. The surface modification layer may contain, for example, Sr or a compound containing Sr. An example of the compound containing Sr is SrO2. The surface modification layer may further contain at least one selected from Al or a compound containing Al, and a compound containing Sr and Al. An example of the compound containing Al is Al2O3. An example of the compound containing Sr and Al is SrAlO4. The surface modification layer may further contain Li. Li present on the surface of the lithium transition metal composite oxide described later may be contained in the surface modification layer.

[0033] The ratio of Al to the total number of moles of metal elements excluding Li in the surface modification layer can be greater than the ratio of Al to the total number of moles of metal elements excluding Li in the main body of the lithium transition metal composite oxide.

[0034] The ratio of Al to the total number of moles of metal elements excluding Li in the surface modification layer is preferably 1.9 times or more the ratio of Al to the total number of moles of metal elements excluding Li in the main body of the lithium transition metal composite oxide.

[0035] The ratio of Sr in the surface modification layer can be 0.05 mol % to 0.25 mol % based on the total number of moles of metal elements other than Li in the surface modification layer. Within this range, the surface state of the lithium transition metal composite oxide can be changed by electronic interaction.

[0036] The thickness of the surface modification layer is, for example, 0.1 nm to 2 nm. If the thickness is within this range, the reaction between the surface of the lithium transition metal composite oxide and the electrolyte is suppressed, and therefore, due to the synergistic effect with the above-mentioned surface layer, the decrease in battery capacity accompanying charge and discharge can be suppressed.

[0037] The amount of Li remaining on the surface of the lithium transition metal composite oxide (hereinafter sometimes referred to as the residual Li amount) can be 0.03 wt% to 0.08 wt%. The Li present on the surface of the lithium transition metal composite oxide includes Li contained in the surface modification layer and Li present not contained in the surface modification layer, for example in the form of a Li compound present on the surface modification layer.

[0038] The positive electrode active material is dispersed in water, dissolved, and the amount of residual Li can be quantified by titration. The specific measurement method is as follows. (1) 1 g of the positive electrode active material is added to 30 ml of pure water and stirred to prepare a suspension in which the active material is dispersed in water. (2) The suspension is filtered, and purified water is added to make up to 70 ml, to obtain a filtrate containing the Li dissolved from the active material. (3) While measuring the pH of the filtrate, add small amounts of hydrochloric acid dropwise to the filtrate, and calculate the amount of Li dissolved in the filtrate from the amount of hydrochloric acid consumed (titration amount) up to the first inflection point (around pH 8) and the second inflection point (around pH 4) on the pH curve.

[0039] The content of the lithium transition metal composite oxide in the positive electrode active material is preferably 90 mass% or more, and more preferably 99 mass% or more, relative to the total mass of the positive electrode active material, from the standpoint of, for example, improving the battery capacity and effectively suppressing deterioration of the charge / discharge cycle characteristics.

[0040] The positive electrode active material of the present embodiment may contain other lithium transition metal composite oxides in addition to the lithium transition metal composite oxide of the present embodiment, such as lithium transition metal composite oxides having a Ni content of 0 mol % or more and less than 85 mol %.

[0041] Next, an example of a method for producing a positive electrode active material including a lithium transition metal composite oxide and a surface modification layer will be described.

[0042] The method for producing a positive electrode active material includes, for example, a first step of obtaining a composite oxide containing Ni, Al, and an arbitrary metal element, a second step of mixing the composite oxide obtained in the first step with a lithium compound to obtain a mixture, and a third step of firing the mixture. Each parameter of the composition and thickness of the surface layer and the surface modification layer in the finally obtained positive electrode active material is adjusted by controlling, for example, the mixing ratio of the raw materials in the second step, the firing temperature and time in the third step, etc.

[0043] In the first step, for example, while stirring a solution of a metal salt containing Ni, Al, and an arbitrary metal element (Co, Mn, Fe, etc.), an alkaline solution such as sodium hydroxide is dropped to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (co-precipitating) a composite hydroxide containing Ni, Al, and the arbitrary metal element, and the composite hydroxide is calcined to obtain a composite oxide containing Ni, Al, and the arbitrary metal element. The calcination temperature is not particularly limited, but is, for example, in the range of 300°C to 600°C.

[0044] In the second step, the composite oxide obtained in the first step is mixed with a lithium compound and a strontium compound to obtain a mixture. Examples of the lithium compound include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. Examples of the strontium compound include Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCo3, SrSO4, and Sr(NO3)2. The mixing ratio of the composite oxide obtained in the first step and the lithium compound is preferably such that the molar ratio of metal elements other than Li to Li is in the range of 1:0.98 to 1:1.1, in order to easily adjust each of the parameters to the ranges specified above. In addition, the mixing ratio of the composite oxide obtained in the first step and the strontium compound is preferably, for example, such that the molar ratio of metal elements other than Li:Sr is in the range of 1:0.0005 to 1:0.0018, in order to facilitate the adjustment of each of the above parameters to the ranges specified above. In the second step, when the composite oxide obtained in the first step, the lithium compound, and the strontium compound are mixed, other metal raw materials may be added as necessary. The other metal raw materials are oxides containing metal elements other than the metal elements constituting the composite oxide obtained in the first step, etc.

[0045] In the third step, the mixture obtained in the second step is fired at a predetermined temperature and time to obtain the positive electrode active material according to this embodiment. The firing of the mixture in the third step includes a first firing step in which the mixture is fired in a firing furnace under oxygen flow at a first heating rate to a first set temperature of 450°C or more and 680°C or less, and a second firing step in which the fired product obtained by the first firing step is fired in a firing furnace under oxygen flow at a second heating rate to a second set temperature of more than 680°C and 800°C or less. Here, the first heating rate is in the range of 1.5°C / min to 5.5°C / min, and the second heating rate is slower than the first heating rate and is in the range of 0.1°C / min to 3.5°C / min. By such multi-stage firing, the parameters of the composition and thickness of the surface layer and the surface modification layer in the finally obtained positive electrode active material of this embodiment can be adjusted to the above-specified range. The first heating rate and the second heating rate may be set in a plurality of rates for each temperature range, so long as they are within the ranges specified above. The holding time of the first set temperature in the first firing step is preferably 0 hours or more and 5 hours or less, more preferably 0 hours or more and 3 hours or less, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the first set temperature is the time during which the first set temperature is maintained after the first set temperature is reached. The holding time of the second set temperature in the second firing step is preferably 1 hour or more and 10 hours or less, more preferably 1 hour or more and 5 hours or less, in terms of adjusting each of the parameters of the lithium transition metal composite oxide to the ranges specified above. The holding time of the second set temperature is the time during which the second set temperature is maintained after the second set temperature is reached. When firing the mixture, in terms of adjusting each of the parameters to the ranges specified above, the firing is performed, for example, in an oxygen stream with an oxygen concentration of 60% or more, and the flow rate of the oxygen stream is set to 10 cm / s of the firing furnace. 3 The flow rate can be in the range of 0.2 mL / min to 4 mL / min per kg of mixture and 0.3 L / min or more per kg of mixture.

[0046] The molar fraction of the metal element contained in the positive electrode active material obtained above was measured by inductively coupled plasma (ICP) emission spectrometry and was expressed by the general formula Li a Ni x Al y Coz M w Sr α O 2-b (wherein, 0.95 < a < 1.05, 0.8 ≤ x ≤ 0.96, 0 < y ≤ 0.10, 0 ≤ z ≤ 0.15, 0 ≤ w ≤ 0.1, 0.05 ≤ α ≤ 0.18, 0 ≤ b < 0.05, x + y + z + w = 1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn). Note that Sr is not dissolved in the lithium transition metal composite oxide but is contained in the surface modification layer present on the surface of the lithium transition metal composite oxide. Also, a part of Al may be contained in the surface modification layer.)

[0047] Further, the composition of the interior and surface layer of the lithium transition metal composite oxide in the positive electrode active material, as well as the composition of the surface modification layer, can be measured for the proportion of Ni, Co, Al, and M by analyzing each location in the cross-section of the primary particles of the positive electrode active material using energy dispersive X-ray spectroscopy (TEM-EDX). Note that since the surface modification layer is thinner than the spot diameter of the electron beam to be irradiated, the composition of the surface modification layer is affected by the composition of the adjacent surface layer. Even if Ni, Co, and Mn are detected in the measurement result of the surface layer, it is considered that Ni, Co, and M do not actually exist in the surface layer. Also, since the addition amount of Sr is small like α above, the presence or absence can be confirmed but it cannot be quantitatively measured.)

[0048] [Negative Electrode] The negative electrode 12 has a negative electrode current collector 40 and negative electrode active material layers 41 formed on both surfaces of the negative electrode current collector 40. As the negative electrode current collector 40, a foil of a metal stable within the potential range of the negative electrode 12 such as copper or a copper alloy, or a film having such a metal disposed on the surface layer can be used. The negative electrode active material layer 41 contains a negative electrode active material and a binder. The thickness of the negative electrode active material layer 41 is, for example, 10 μm to 150 μm on one side of the negative electrode current collector 40. The negative electrode 12 can be produced by applying a negative electrode slurry containing a negative electrode active material, a binder, etc. on the surface of the negative electrode current collector 40, drying the coating film, and then rolling to form the negative electrode active material layer 41 on both surfaces of the negative electrode current collector 40.)

[0049] The negative electrode active material contained in the negative electrode active material layer 41 is not particularly limited as long as it can reversibly occlude and release lithium ions. Generally, carbon materials such as graphite are used. The graphite may be any of natural graphite such as flaky graphite, massive graphite, and earthy graphite, massive artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads. Further, as the negative electrode active material, metals that alloy with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. may be used. Further, those provided with a carbon coating may be used. For example, SiO x (0.5 ≦ x ≦ 1.6), or Li 2y SiO (2+y) A Si-containing compound in which fine particles of Si are dispersed in a lithium silicate phase represented by (0 < y < 2) may be used in combination with graphite.

[0050] As the binder contained in the negative electrode active material layer 41, similar to the case of the positive electrode 11, fluorine-containing resins such as PTFE and PVdF, PAN, polyimide, acrylic resin, polyolefin, etc. may be used, but preferably styrene-butadiene rubber (SBR) is used. Further, the negative electrode active material layer 41 may contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc.

[0051] [Separator] For the separator 13, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous thin films, woven fabrics, non-woven fabrics, etc. As the material of the separator, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 may have a single-layer structure or a laminated structure. Further, a resin layer with high heat resistance such as an aramid resin, a filler layer containing an inorganic compound filler may be provided on the surface of the separator 13.

[0052] [Non-aqueous electrolyte] The non-aqueous electrolyte includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. Examples of the halogen-substituted product include fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, and fluorinated chain carboxylates such as methyl fluoropropionate (FMP).

[0053] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).

[0054] Examples of the above ethers include cyclic ethers such as 1,3 - dioxolane, 4 - methyl - 1,3 - dioxolane, tetrahydrofuran, 2 - methyltetrahydrofuran, propylene oxide, 1,2 - butylene oxide, 1,3 - dioxane, 1,4 - dioxane, 1,3,5 - trioxane, furan, 2 - methylfuran, 1,8 - cineole, crown ether, etc.; and chain ethers such as 1,2 - dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o - dimethoxybenzene, 1,2 - diethoxyethane, 1,2 - dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1 - dimethoxymethane, 1,1 - diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, etc.

[0055] The electrolyte salt is preferably a lithium salt. Examples of the lithium salt include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), etc.; LiN(SO2CF3)2, LiN(C1F 2l+1 SO2)(C m F 2m+1Examples of the lithium salt include imide salts such as LiPF6, LiPF2, and the like (wherein l and m are integers of 0 or more). The lithium salt may be used alone or in combination of two or more. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is, for example, 0.8 mol to 1.8 mol per 1 L of the non-aqueous solvent. Furthermore, vinylene carbonate or a propane sultone-based additive may be added. EXAMPLES

[0056] The present disclosure will be further described below with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.

[0057] [Preparation of positive electrode active material] <Example 1> [Ni 0.82 Al 0.05 Co 0.13 The composite hydroxide represented by the formula ](OH)2 was calcined at 500°C for 8 hours to obtain the composite oxide (Ni 0.82 Al 0.05 Co 0.13 LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Al, and Co to Sr was 1.03:1:0.0005 to obtain a mixture. The mixture was then heated under an oxygen flow (10 cm) with an oxygen concentration of 95%. 3 The mixture was fired at a temperature rise rate of 2.0°C / min from room temperature to 650°C, and then fired at a temperature rise rate of 0.5°C / min from 650°C to 780°C under a flow rate of 2 mL / min per kg of mixture and 5 L / min per kg of mixture. The fired product was washed with water to remove impurities, and a positive electrode active material was obtained. The composition of the positive electrode active material obtained above was measured using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, product name "iCAP6300"), and the composition was found to be LiNi 0.82 Al 0.05 Co 0.13 Sr 0.0005 This was used as the positive electrode active material of Example 1.

[0058] <Comparative Example 1> LiOH and composite oxide (Ni 0.82 Al 0.05 Co 0.13 A positive electrode active material was obtained in the same manner as in Example 1, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Al, and Co was 1.03:1. 0.82 Al 0.05 Co 0.13 This was used as the positive electrode active material of Comparative Example 1.

[0059] <Example 2> [Ni 0.87 Al 0.04 Co 0.09 ](OH)2 was used to obtain a composite oxide (Ni 0.87 Al 0.04 Co 0.09 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Al, and Co to Sr was 1.03:1:0.001 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.87 Al 0.04 Co 0.09 Sr 0.001 This was used as the positive electrode active material of Example 2.

[0060] <Comparative Example 2> LiOH and composite oxide (Ni 0.87 Al 0.04 Co 0.09 A positive electrode active material was obtained in the same manner as in Example 2, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Al, and Co was 1.03:1. 0.87 Al 0.04 Co 0.09 This was used as the positive electrode active material of Comparative Example 2.

[0061] <Example 3> [Ni 0.92 Al 0.05 Co 0.01 Mn 0.02](OH)2 was used to obtain a composite oxide (Ni 0.92 Al 0.05 Co 0.01 Mn 0.02 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Al, Co, and Mn to Sr was 1.03:1:0.0007. 0.92 Al 0.05 Co 0.01 Mn 0.02 Sr 0.0007 This was used as the positive electrode active material of Example 3.

[0062] <Comparative Example 3> LiOH and composite oxide (Ni 0.92 Al 0.05 Co 0.01 Mn 0.02 A positive electrode active material was obtained in the same manner as in Example 3, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Al, Co, and Mn was 1.03:1. 0.92 Al 0.05 Co 0.01 Mn 0.02 This was used as the positive electrode active material of Comparative Example 3.

[0063] <Example 4> [Ni 0.91 Al 0.05 Mn 0.04 ](OH)2 was used to obtain a composite oxide (Ni 0.91 Al 0.05 Mn 0.04 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Al, and Mn to Sr was 1.03:1:0.0015 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.91 Al 0.05 Mn 0.04 Sr 0.0015This was used as the positive electrode active material of Example 4.

[0064] <Comparative Example 4> LiOH and composite oxide (Ni 0.91 Al 0.05 Mn 0.04 A positive electrode active material was obtained in the same manner as in Example 4, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Al, and Mn was 1.03:1. 0.91 Al 0.05 Mn 0.04 This was used as the positive electrode active material of Comparative Example 4.

[0065] <Example 5> [Ni 0.92 Al 0.06 Mn 0.02 ](OH)2 was used to obtain a composite oxide (Ni 0.92 Al 0.06 Mn 0.02 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Al, and Mn to Sr was 1.03:1:0.0018 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.92 Al 0.06 Mn 0.02 Sr 0.0018 This was used as the positive electrode active material of Example 5.

[0066] <Comparative Example 5> LiOH and composite oxide (Ni 0.92 Al 0.06 Mn 0.02 A positive electrode active material was obtained in the same manner as in Example 5, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Al, and Mn was 1.03:1. 0.92 Al 0.06 Mn 0.02 This was used as the positive electrode active material of Comparative Example 5.

[0067] <Comparative Example 6> [Ni 0.60 Co 0.21 Mn 0.19 ](OH)2 was used to obtain a composite oxide (Ni 0.60 Co 0.21 Mn 0.19 A positive electrode active material was obtained in the same manner as in Example 1, except that LiOH, Sr(OH)2, and the above composite oxide were mixed so that the molar ratio of the total amount of Li, Ni, Co, and Mn to Sr was 1.03:1:0.001 to obtain a mixture. The composition of the obtained positive electrode active material was LiNi 0.60 Co 0.21 Mn 0.19 Sr 0.001 This was used as the positive electrode active material of Comparative Example 6.

[0068] <Comparative Example 7> LiOH and composite oxide (Ni 0.60 Co 0.21 Mn 0.19 A positive electrode active material was obtained in the same manner as in Comparative Example 6, except that Li was mixed with O2) so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.03:1. 0.60 Co 0.21 Mn 0.19 This was used as the positive electrode active material of Comparative Example 7.

[0069] The positive electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 7 were subjected to TEM-EDX measurement, and composition analysis was performed on the inside and surface layer of the lithium transition metal composite oxide, and on the surface modification layer. Since Sr could not be quantified, the presence or absence of Sr was analyzed from the presence or absence of a peak. In addition, the amount of residual Li in the positive electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 7 was measured. The results are shown in Table 1.

[0070] [Table 1]

[0071] In Examples 1 to 5, the Al content of the surface modification layer was higher than the Al content of the main body and the Al content of the surface layer. On the other hand, in Comparative Examples 1 to 5, such a tendency was not observed. In Examples 1 to 5, the Al content of the surface modification layer was higher than that of the surface layer, and Al was present in the surface modification layer, but in Comparative Examples 1 to 5, the Al content of the surface modification layer and the surface layer was approximately the same, so it is considered that Al is affected by the composition of the adjacent surface layer and that Al is not present in the surface modification layer. In Examples 1 to 5 and Comparative Example 6 in which Sr was added, Sr was detected only in the surface modification layer and not in the surface layer or the main body. In addition, in all samples, the composition of the surface modification layer was affected by the composition of the adjacent surface layer, and Ni, Co, and Mn are considered not to be present in the surface modification layer. In addition, residual Li was detected in all samples.

[0072] Next, test cells were fabricated as follows using the positive electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 7.

[0073] [Preparation of positive electrode] The positive electrode active material of Examples 1 to 5 and Comparative Examples 1 to 7 was mixed in a ratio of 91 parts by mass, 7 parts by mass of acetylene black as a conductive material, and 2 parts by mass of polyvinylidene fluoride as a binder, and this was mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Next, the slurry was applied to a positive electrode current collector made of aluminum foil with a thickness of 15 μm, and after drying the coating film, the coating film was rolled with a rolling roller and cut into a predetermined electrode size to obtain a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode core. In addition, an exposed portion in which the surface of the positive electrode core was exposed was provided in a part of the positive electrode. Positive electrodes were also prepared in the same manner in other Examples and Comparative Examples.

[0074] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a rolling roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.

[0075] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0076] [Preparation of test cell] An aluminum lead was attached to the exposed part of the positive electrode containing the positive electrode active material of Examples 1 to 5 and Comparative Examples 1 to 7, and a nickel lead was attached to the exposed part of the negative electrode, and the positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween to prepare a wound electrode body. This electrode body was placed in an exterior body, and the nonaqueous electrolyte was injected, and then the opening of the exterior body was sealed to obtain a test cell.

[0077] [Evaluation of capacity retention rate] The following cycle test was carried out on the batteries prepared by incorporating the positive electrodes containing the positive electrode active materials of Examples 1 to 5 and Comparative Examples 1 to 7. The discharge capacity at the first cycle and the discharge capacity at the 100th cycle of the cycle test were determined, and the capacity retention rate was calculated by the following formula.

[0078] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity amount)×100 <Cycle test> The test cell was charged at a constant current of 0.5 It in a temperature environment of 45°C until the battery voltage reached 4.2 V, and then charged at a constant voltage until the current value reached 1 / 50 It at 4.2 V. Then, the test cell was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 100 times.

[0079] The capacity retention rates of Examples 1 to 5 and Comparative Examples 1 to 7 are shown in Tables 2 to 7. The amount of residual Li is also shown in Tables 2 to 7. The capacity retention rate of the test cell of Example 1 shown in Table 2 is shown relatively to the capacity retention rate of the test cell of Comparative Example 1, which is set as 100%.

[0080] The capacity retention rates of the test cells of Example 2 shown in Table 3 are expressed relatively to the capacity retention rate of the test cells of Comparative Example 2, which is set to 100%.

[0081] The capacity retention rates of the test cells of Example 3 shown in Table 4 are expressed relatively to the capacity retention rate of the test cells of Comparative Example 3, which is set at 100%.

[0082] The capacity retention rates of the test cells of Example 4 shown in Table 5 are expressed relatively to the capacity retention rate of the test cells of Comparative Example 4, which is set to 100%.

[0083] The capacity retention rate of the test cell of Example 5 shown in Table 6 is expressed relatively to the capacity retention rate of the test cell of Comparative Example 5, which is set to 100%.

[0084] The capacity retention rate of the test cell of Comparative Example 7 shown in Table 7 is expressed relatively to the capacity retention rate of the test cell of Comparative Example 6, which is set to 100%.

[0085] [Table 2]

[0086] [Table 3]

[0087] [Table 4]

[0088] [Table 5]

[0089] [Table 6]

[0090] [Table 7]

[0091] In all of Tables 2 to 6, the examples containing Sr in the surface modification layer had a higher capacity retention rate than the comparative examples not containing Sr in the surface modification layer. It is presumed that the surface layer contains more Al than the main body, and furthermore, a part of Al is contained in the surface modification layer. In Table 7, the lithium transition metal composite oxides in both Comparative Examples 6 and 7 do not contain Al, so there was no change in the capacity retention rate with or without the addition of Sr. [Explanation of symbols]

[0092] REFERENCE SIGNS LIST 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode tab, 21 negative electrode tab, 22 grooved portion, 23 bottom plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 positive electrode current collector, 31 positive electrode active material layer, 40 negative electrode current collector, 41 negative electrode active material layer

Claims

1. a lithium transition metal composite oxide containing at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li; a surface modification layer formed on the surface of the primary particles of the lithium transition metal composite oxide and containing at least Sr; The positive electrode active material for a non-aqueous electrolyte secondary battery comprises Sr which is not dissolved in the lithium transition metal composite oxide.

2. a lithium transition metal composite oxide containing at least 80 mol % or more of Ni and Al relative to the total number of moles of metal elements excluding Li; a surface modification layer formed on the surface of the primary particles of the lithium transition metal composite oxide, the surface modification layer containing at least Sr and Al; The lithium transition metal composite oxide has the general formula Li a Ni x A y Co z M w O 2-b 2. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, represented by the formula: (wherein 0.95<a<1.05, 0.8≦x≦0.96, 0<y≦0.10, 0≦z≦0.15, 0≦b<0.05, x+y+z+w=1, and M is at least one element selected from Mn, Fe, Ti, Si, Nb, Zr, Mo, and Zn).

3. The lithium transition metal composite oxide has a surface layer present from the surface to the inside, and a main body portion present on the inside side of the surface layer, 3. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio of Al to a total number of moles of metal elements excluding Li in the surface modification layer is greater than a ratio of Al to a total number of moles of metal elements excluding Li in the main body.

4. 4. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 3, wherein a ratio of Al to a total number of moles of metal elements excluding Li in the surface layer is 1.3 times or more a ratio of Al to a total number of moles of metal elements excluding Li in the main body.

5. 5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein a ratio of Sr in the surface modification layer is 0.05 mol % to 0.25 mol % with respect to a total number of moles of metal elements excluding Li in the surface modification layer.

6. 6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the ratio of Ni to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide is 90 mol % or more.

7. 7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the amount of Li remaining on the surface of the lithium transition metal composite oxide is 0.03 wt % to 0.08 wt %.

8. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 7, a negative electrode, and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Modified precursor for lithium ion battery, positive electrode material and preparation method of precursor and positive electrode material

    CN109455772A

  • Lithium-nickel composite oxide, lithium-ion secondary battery using it, and manufacturing method of lithium-nickel composite oxide

    JP2009129820A

  • Nonaqueous secondary battery

    JP2013254639A

  • Non-aqueous electrolyte battery

    WO2019031117A1

  • Positive electrode active material for nonaqueous electrolyte secondary batteries, method for producing positive electrode active material for nonaqueous electrolyte secondary batteries, and method for evaluating lithium metal composite oxide powder

    WO2019087558A1